Microbiological analysis of the gut content in the fish from the fishpond of Lukovo - Belichovska Katerina, Belichovska Daniela, Pejkovski Zlatko, Uzunoska Zora, Duraku Suzana (Institute of Knowledge Menagament, Skopje, 2016)
Fishpond „Lukovo“ is located in the village of Lukovo, Struga. Rainbow trout (Oncorhynchus mykiss Walbaum) has been grown in it. It is supplied with spring water. The fishpond has an area of 800 m2. During the months of June, July and January microbiological testing of the gastrointestinal tract content of fish were carried out. Coliform bacteria and Escherichia coli were found in June and July. It is recommended more frequently cleaning the fish ponds and hygienic control of food safety.
Keywords: fish, digestive tract, microbiological analysis